The aequitas contributionis as a basis for the prohibition of enriching oneself with the detriment of others in the lex Rhodia de iactu: Peer-reviewed article (Italian Review of Legal History, 2023)
Previous considerations on the contracts environment for maritime transport of goods in the Roman commercial praxis, the present research addresses the criterion of the aequitas contributionis and its intrinsic relation with the prohibition of enriching oneself with the detriment of others in the lex Rhodia de iactu. In fact, by means of this nautical custom, the owners of the transported goods that were saved from the ejection, in the wake of the periculum of the sinking of the vessel, had to compensate those tenants who lost theirs, in order to restore the broken patrimonial aequitas among the tenants of the transport service for the iactus mercium. This reestablishment was made effective through the procedural actions that arose from the locatio conductio operis stipulated between the vectores and the magister navis, in addition to the ius retentionis legal remedies in favour of the last one. And, based on the aforementioned mechanisms, the iudex proceeded to determine (aestimatio) the quantum contributionis.
Keywords: Aequitas contributionis; lex Rhodia de iactu; locatio conductio operis; ius retentionis